2017
DOI: 10.1111/ajt.14279
|View full text |Cite
|
Sign up to set email alerts
|

Allo-HLA Cross-Reactivities of Cytomegalovirus-, Influenza-, and Varicella Zoster Virus–Specific Memory T Cells Are Shared by Different Healthy Individuals

Abstract: Virus-specific T cells can recognize allogeneic HLA (allo-HLA) through TCR cross-reactivity. The allospecificity often differs by individual (private cross-reactivity) but also can be shared by multiple individuals (public cross-reactivity); however, only a few examples of the latter have been described. Because these could facilitate alloreactivity prediction in transplantation, we aimed to identify novel public cross-reactivities of human virus-specific CD8 T cells directed against allo-HLA by assessing thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…Another option could be that cells other than CD8+ T cells (i.e., CMV-specific Th1 CD4+ T cells) can produce IFNG in the QF assay, since it has been reported that the peptide length distinction is not absolute and CD4+ T cells can be stimulated by antigen presented on HLA class I molecules 26 . Other alternative explanations could be related to the cross-reactivity with T cells specific for other herpes viruses or unrelated viruses 27,28 or even that the 24 h stimulation of the QF assay led to the in vitro priming of CD8+ T cells 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Another option could be that cells other than CD8+ T cells (i.e., CMV-specific Th1 CD4+ T cells) can produce IFNG in the QF assay, since it has been reported that the peptide length distinction is not absolute and CD4+ T cells can be stimulated by antigen presented on HLA class I molecules 26 . Other alternative explanations could be related to the cross-reactivity with T cells specific for other herpes viruses or unrelated viruses 27,28 or even that the 24 h stimulation of the QF assay led to the in vitro priming of CD8+ T cells 19 .…”
Section: Discussionmentioning
confidence: 99%
“…12 Moreover, Heuvel and others have described methods using tetramer-based mixed lymphocyte reactions to more specifically define antigen-specific TCRs for common vaccine and pathogenic peptides that cross-react with specific donor HLA alleles across multiple healthy individuals. 16,17 The goal of these investigations is to ultimately be able to define the risk of allo-cross-reactive T-cell memory present within a given patient prior to transplantation; however, this approach is currently limited by the availability of reagents and the extensive combinatorial diversity of peptide/MHC that is presented in each individual upon infection, as well as TCR diversity. 16,17 The goal of these investigations is to ultimately be able to define the risk of allo-cross-reactive T-cell memory present within a given patient prior to transplantation; however, this approach is currently limited by the availability of reagents and the extensive combinatorial diversity of peptide/MHC that is presented in each individual upon infection, as well as TCR diversity.…”
Section: Heterologous Immunity To Microbial or Environmental Antigensmentioning
confidence: 99%
“…13,14 These "public" cross-reactive TCRs were identified using common antigens from cytomegalovirus, influenza A, Epstein Barr, and Varicella Zoster, which are all relatively ubiquitous in the human population. 16,17 The goal of these investigations is to ultimately be able to define the risk of allo-cross-reactive T-cell memory present within a given patient prior to transplantation; however, this approach is currently limited by the availability of reagents and the extensive combinatorial diversity of peptide/MHC that is presented in each individual upon infection, as well as TCR diversity. Identifying the "private" cross-reactive TCR/allo-HLA combinations for every patient before a transplant would assuredly be extremely challenging; nevertheless, expanding the data on public cross-reactivities provides a layer of information that could be used to improve risk-stratification of patients at risk for acute memory T-cell-mediated rejection.…”
Section: Heterologous Immunity To Microbial or Environmental Antigensmentioning
confidence: 99%
“…Recently, it has been recognized that these virus-specific memory T cells may be cross-reactive sometimes mediated by a public TCR shared by unrelated individuals. 121 …”
Section: Immune Mechanisms Of Im-adrsmentioning
confidence: 99%